2012
DOI: 10.1111/j.1539-6924.2012.01893.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Uncertain Map Features on Risk Beliefs and Perceived Ambiguity for Maps of Modeled Cancer Risk from Air Pollution

Abstract: Maps are often used to convey information generated by models, for example, modeled cancer risk from air pollution. The concrete nature of images, such as maps, may convey more certainty than warranted for modeled information. Three map features were selected to communicate the uncertainty of modeled cancer risk: (a) map contours appeared in or out of focus, (b) one or three colors were used, and (c) a verbal-relative or numeric risk expression was used in the legend. Study aims were to assess how these featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 67 publications
2
43
1
Order By: Relevance
“…Previously unanalyzed data on adequacy judgments, collected as part of the Severtson and Myers (2013) study, were used to address study aims. The full factorial 2 × 2 × 2 × 4 study (resulting in 32 study maps) was designed to test how three dichotomous map features across four cancer risk levels influenced dependent variables.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously unanalyzed data on adequacy judgments, collected as part of the Severtson and Myers (2013) study, were used to address study aims. The full factorial 2 × 2 × 2 × 4 study (resulting in 32 study maps) was designed to test how three dichotomous map features across four cancer risk levels influenced dependent variables.…”
Section: Methodsmentioning
confidence: 99%
“…This decreases the need to consult the legend in order to understand the symbol’s meaning, which facilitates comprehension (Robinson & Petchenik, 1976). Features proposed to foster bottom-up comprehension of magnitude (Cleveland & McGill, 1985) iconically resemble magnitude to some extent, such as incremental shading or incremental length to convey incremental magnitude (Severtson & Myers, 2013). Cartographers recommend using incrementally darker color shades on maps to represent incremental magnitudes of a phenomenon (Brewer, 2006).…”
Section: Theoretical Conceptsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results suggest that visualisation of hazard data on a map can influence the information that people take away. Modified from Thompson et al (2015) wildfire (e.g., Cheong et al 2016), hurricane (e.g., Broad et al 2007;Sherman-Morris et al 2015), flooding (e.g., Strathie et al 2015), sea level rise (e.g., Retchless 2014), and health (e.g., Severtson and Myers 2013). For example, researchers have found that visual design of wildfire hazard maps can influence people's interest and engagement with the hazard information and also how they use it to make decisions about evacuation (Cao et al 2016;Cheong et al 2016).…”
Section: Exploring and Testing Different Designsmentioning
confidence: 99%